Infant and Young Child Feeding Practice among Mothers in Rural Areas of Gazipur District, Bangladesh - Hossain, Md Anwar; Nazneen, Humaira; Sharmin, Saida; Chowdhury, Ayesha Mahzabin; Afrin, Atia (Community Based Medical Journal, 2024)
A cross-sectional, descriptive study was conducted among 599 mothers who had at least one child aged 0–23-month to determine infant and young child feeding practice (IYCF) in rural areas of Bangladesh. The study was conducted between November 2019 and March 2020 in rural areas of Gazipur district. A pre-tested semi-structured questionnaire was used to collect data. Out of 599 respondents, the majority (62.93%) were in the 21-30 years age-group. Only 6.67% were illiterate and the rest of the respondents were literate with different levels of education. About one third (33.38%) of the respondents had monthly income between BDT 5001- 15000. 27% of the mothers could not give colostrum to the babies; half of them (50%) mentioned that baby could not suck well, while 43.83% mentioned being advised by the elders (not to give colostrum) and 6.17% mentioned their own illness. Pre-lacteal feeding practice was observed among 27% mothers and common pre-lacteal food was honey (61.25%), sugar water (35.63%) and animal milk (4.32%). Breastfeeding was initiated within the first hour of birth among 73.29% of mothers. 53.26% percent of mothers practice exclusive breastfeeding (EBF). Difficulties faced by mothers for EBF are insufficient secretion of breast milk (46.42%), not having knowledge about EBF (42.51%), and mother’s illness (11.07%). Most of the mothers (81.63%) gave complementary feeding in the correct time (6 months) and predominant complementary food was Khichuri (51.91%); however, most of them (60.77%) gave complementary food ≤3 times in a day. Our data suggests that the practice of IYCF was not optimum among the rural mothers. To improve this condition, it is necessary to motivate mothers through proper health education about the positive impacts of IYCF on child health. CBMJ 2024 January: vol. 13 no. 01 P: 28-34